Chapter «Débarquer/démarquer»: Voltaire e Magellano - Landi, Michela (Studi e saggi, 2021)
Following Voltaire's Essai sur les mœurs, the first explorers of the new worlds are innocents: they respond to the mythic imagery of the first man. It is on their successors that lays the blame: interested in material enrichment, they despoil the new world. After Magellan, the first geographical demarcation line having been overcome, the culture degeneration of Western world is double: geographic and hermeneutic. Voltaire is in fact not so far from Rousseau's thinking.